Effectiveness of Problem-Based Learning Model on Critical Thinking Ability in Financial Management Course - Saut Maruli Tua Pandiangan; Victor Pattiasina; Badriatul Mawadah; Donny Dharmawan; Suratminingsih Suratminingsih (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this research is to analyze effectiveness of problem-based learning model on critical thinking ability in financial management course. This type of research applies a quantitative approach. Population in the study are students at Medan City Private Universities. Based on needs and cost efficiency, sample in this study is 30 respondents. Hypothesis testing uses partial test. The research results show that application of problem-based learning model is felt to be quite effective in making students more active in participating in learning, thereby fostering students' ability to think critically in financial management courses. Statistically, it shows that problem-based learning model has a significant effect on critical thinking ability in financial management course.